Estudos empíricos sobre a abordagem SMartySPEM para gerência de variabilidades em linhas de processo de software - Pazin, Maicon Giovane (2017)
Assimilating the diversity and complexity of software systems with the heterogeneity of professionals teams who develop such systems has always been one of the great challenges faced by software engineering. For this, it is necessary to define, reuse and constantly improve software processes that organize daily tasks, helping improve quality and increase the productivity of such teams. However, software processes maintaining and reusing is not a simple task. In this scenario, software process modeling languages (SPML) are important because they clearly describe the activities, tasks, roles, artifacts, and tools of these processes. In order to systematically manage the variability found during the maintenance and reuse of software processes, recent studies propose techniques and tools based on Software Process Line (SPrL). Although this research area is still not consolidated, several approaches found in the literature can be considered promising, as SMartySPEM. This approach proposes a mechanism to represent variability in SPrL. It is based on the SPEM metamodel for process modeling and on SMarty to aid in the management of variabilities. This work presents a set of empirical studies aimed at evaluating the SMartySPEM approach, providing initial evidence on the feasibility and effectiveness of its variability mechanism. For this, the Sequential Explanatory Strategy based on Mixed Methods of research was adopted. The results present relevant evidence on the feasibility and effectiveness of SMartySPEM, proposes the evolution of such an approach, as well as new artifacts for future work related to the SPrL area.